If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k9+3=14
We move all terms to the left:
k9+3-(14)=0
We add all the numbers together, and all the variables
k^9-11=0
We do not support ekpression: k^9
| 6x+10=5(2-7x) | | 3n+4=2n+2 | | -3x=-39;x=13 | | 3(u-6)-3=-3(-4u=6)-3u | | 5(+9-2(1-r=1 | | 2v+44=-2(v-4) | | 5x+9=1x+15 | | 4800-500x=0 | | 31-x=-4;x=35 | | x-20=4x-5 | | 7(4x+7)=3+4(-4-6x) | | -4(u+6)=-6u-22 | | 7(b-90)=35 | | X2+5x-32=2x-4 | | -5/6x-1/9x=2 | | (b/7)+(1/4)=19 | | 31+119+x=150 | | -3.4+v/5=-15.9 | | 4(x-6)+4=6x+2(x-6) | | –(7x–2+12)+(-5x–3x+4)=–(-x+7)–(6x–4–7) | | 6(-3)+3y=9 | | 2x2+19x+9=0 | | 2=3x=19/5 | | 2x+7-24=100+4x | | 5(x-2)+6x=7x+4(x-6) | | s/9+26=29 | | –11g=18−20g | | N2/5+2n/6=12 | | (5x-15)+(8x-8)=180 | | 16d=14d+18 | | m/7+40=46 | | 186-w=232 |